DEVELOPING PRIMARY SCHOOL STUDENTS' SPEAKING SKILLS THROUGH FOLKLORE - Saipova Hilola Abdulhamitovna; Okhunova Munisa Umidbek kizi (Bright Mind Publishing, 2025)
This article describes the theoretical basis and importance of the formation of speech skills in elementary school students through the works of folk oral works given in the elementary school textbook.
Keywords: Folklore, elementary school, fairy tales, proverbs, folk epics, reading book.